Neuropsychological Decline Stratifies Dementia Risk in Cognitively Unimpaired and Impaired Older Adults - Ho, Jean K.; Nation, Daniel A. (Frontiers in Aging Neuroscience, 2022)
Objective Validation and widespread use of markers indicating decline in serial neuropsychological exams has remained elusive despite potential value in prognostic and treatment decision-making. This study aimed to operationalize neuropsychological decline, termed “neuropsychological (NP) decline,” in older adults followed over 12 months in order to aid in the stratification of dementia risk along the cognitively unimpaired-to-mild cognitive impairment (MCI) spectrum. Methods A prospective cohort study utilized 6,794 older adults from the National Alzheimer’s Coordinating Center (NACC) database with a baseline diagnosis of normal cognition, impaired without MCI or with MCI. Operationalization of NP decline over 12-month follow-up used regression-based norms developed in a robustly normal reference sample. The extent to which each participant’s 12-month follow-up score deviated from norm-referenced expectations was quantified and standardized to an NP decline z-score. Cox regression evaluated whether the NP decline metric predicted future dementia. Results Participant’s NP decline scores predicted future all-cause dementia in the total sample, χ2 = 110.71, hazard ratio (HR) = 1.989, p < 0.001, and in the subset diagnosed with normal cognition, χ2 = 40.84, HR = 2.006, p < 0.001, impaired without MCI diagnosis, χ2 = 14.89, HR = 2.465, p < 0.001, and impaired with MCI diagnosis, χ2 = 55.78, HR = 1.916, p < 0.001. Conclusion Operationalizing NP decline over 12 months with a regression-based norming method allows for further stratification of dementia risk along the cognitively unimpaired-to-MCI spectrum. The use of NP decline as an adjunctive marker of risk beyond standard cognitive diagnostic practices may aid in prognosis and clinical decision-making.